2009
DOI: 10.1007/s11666-009-9325-2
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Aspects of High Velocity Impact of Particles in Cold Spraying by Explicit Finite Element Analysis

Abstract: In this study, an examination of cold spray particle impacting behavior using the ABAQUS/Explicit program was conducted for typical copper material (OFHC). Various combinations of calculation settings concerning element type, Arbitrary Lagrangian Eulerian adaptive meshing, contact interaction, material damage, etc., were examined with the main focus on the element excessive distortion and its effect on the resultant output. The effect of meshing size on the impact behavior was also clarified compared to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 13 publications
0
59
0
1
Order By: Relevance
“…In addition, considering the fast dynamics and large deformation during the particle/substrate impact, the control of excessive element distortions is required to ensure integration stability ( Ref 14,25,30). Particularly for this study, element distortion control is used with the distortion length ratio 0.1 for the large deformation, which is shown to give good description of the deformation and temperature evolution (see Supplementary Information for details).…”
Section: Materials Properties and Fea Controlling Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, considering the fast dynamics and large deformation during the particle/substrate impact, the control of excessive element distortions is required to ensure integration stability ( Ref 14,25,30). Particularly for this study, element distortion control is used with the distortion length ratio 0.1 for the large deformation, which is shown to give good description of the deformation and temperature evolution (see Supplementary Information for details).…”
Section: Materials Properties and Fea Controlling Parametersmentioning
confidence: 99%
“…The aforementioned control techniques, however, unavoidably impose artificial constraints, and thus presumably affect the physical behaviors of the material. While many efforts have been made to improve the simulation convergence ( Ref 14,25,31), no study yet explores the influence of deformation control techniques on the onset of shear instability.…”
Section: Introductionmentioning
confidence: 99%
“…Zdecydowano się również na zastosowanie algorytmu ALE adaptive mesh w celu zapobieżenia znacznej deformacji siatki. Okazało się jednak, że podobnie jak w przypadku metali [13,14], algorytm ten nie wpłynął na polepszenie jakości wyników. tablica I. Dane materiałowe zastosowane do symulacji [10,11] Ze względu na późniejszą weryfikację doświad-czalną badań numerycznych zdecydowano się przyjąć parametry nanoszenia możliwe do ustawienia na posiadanym urządzeniu Dymet 413.…”
Section: Materiały I Metodyka Badańunclassified
“…Considering the extremely short impacting time scale, it is difficult to experimentally observe the whole deformation process of particles, only the formed coating can be observed through the experimental way. Therefore, the numerical method was always employed to study the particle deformation process as well as the bonding mechanism in cold spraying ( Ref 6,[12][13][14][15][16][17]. It has been reported that particle mechanical properties, particle size, incident velocity, and angle play an important role in the deformation behavior and coating formation ( .…”
Section: Introductionmentioning
confidence: 99%